The Effect of Silencing MiR-4270 on Apoptosis in HCC Cell Line - Gholamia, Hanieh; Akrami, Hassan; Sassan, Hosseinali; Erfani, Nasrollah; Fattahi, Mohammad Reza; Heidari, Mojdeh (Current Signal Transduction Therapy, 2024)
Background: Hepatocellular carcinoma (HCC) is the most common type of cancer. Although HCC treatment has greatly improved over the past few decades, patient survival rates are still very low. Therefore, it is essential to find new treatments for HCC. Apoptosis has been shown to be the most effective in disrupting cancer growth. Improper functioning of proteins in apoptosis can lead to cancer growth. MicroRNAs (miRNAs) are key regulators in the development and progression of HCC. Objective: Irregular expression of miRNAs involved in apoptosis signaling can lead to tumorigenesis. Therefore, we investigated the effect of the hsa-miR-4270 inhibitor on cell proliferation and apoptosis. Methods: HepG2 cells were cultured at 37°C and 95% air. Transfection of HepG2 cells was performed by miR-4270 inhibitor and lipofectamine 2000. Cell proliferation of HepG2 cells was determined with MTT assay and different concentrations of miR-4270 specific inhibitors. DNA laddering assay was performed to evaluate the induction of apoptosis. Finally, the transcription level of genes involved in apoptosis, including BAX, BCL2, Caspase3, and p53, was measured by real-time RT-PCR. Results: The results of MTT and DNA laddering assays showed that the miR-4270 inhibitor declined cell proliferation and induced apoptosis in HepG2 cells. Also, the results of quantitative real-time RT-PCR indicated an upregulation of transcription of BAX, p53 and Caspase3 genes and a decline in expression of BCL2 gene. Conclusion: Taken together, we found hsa-miR-4270 inhibitor decreased cell proliferation and induced apoptosis in the HepG2 cell line, which can be used as a new therapeutic strategy for HCC patients.
Keywords: apoptosis